A note on the posterior inference for the Yule–Simon distribution. Issue 6 (13th April 2017) - Leisen, Fabrizio; Rossini, Luca; Villa, Cristiano
ABSTRACT: The Yule–Simon distribution has been out of the radar of the Bayesian community, so far. In this note, we propose an explicit Gibbs sampling scheme when a Gamma prior is chosen for the shape parameter. The performance of the algorithm is illustrated with simulation studies, including count data regression, and a real data application to text analysis. We compare our proposal to the frequentist counterparts showing better performance of our algorithm when a small sample size is considered.